Spirituality through Music in the Poetry of Francisco Luis Bernárdez - Sarfson, Susana (Madrygal. Revista de Estudios Gallegos, 2023)
The lyrical expression of the Argentine poet Francisco Luis Bernárdez (1900-1978) is developed from a series of influences ranging from modernist and ultraist writers to those of Golden Century of Spanish Poetry. However, as he consolidates his personal voice, three issues emerge as constants in his works: music, the search for sacred and anguish. In the poiesis of this writer, Music manifests itself as vehicle of the spirit. This work exposes and exemplifies these three branches of the same point of interest of the poet: spirituality as the destiny of the human being.